2011
DOI: 10.1097/ijg.0b013e3181efe1d5
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Lens Capsule Versus Mitomycin-C as an Adjunct to Trabeculectomy in Combined Phacotrabeculectomy

Abstract: Anterior lens capsule is effective in phacotrabeculectomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Therefore, we infer the biodegradation of ALC in vivo may occur between 1 and 3 months. Besides our study, several other studies also confirmed the efficacy and safety of ALC transplantation in phacotrabeculectomy (Emarah & El-Helw 2011;Das et al 2018) or phacoemulsification-deep sclerectomy (Rekas et al 2010) thereafter.…”
Section: Application Of Alc In Glaucomasupporting
confidence: 85%
“…Therefore, we infer the biodegradation of ALC in vivo may occur between 1 and 3 months. Besides our study, several other studies also confirmed the efficacy and safety of ALC transplantation in phacotrabeculectomy (Emarah & El-Helw 2011;Das et al 2018) or phacoemulsification-deep sclerectomy (Rekas et al 2010) thereafter.…”
Section: Application Of Alc In Glaucomasupporting
confidence: 85%